A Direct Latent Variable Modeling Based Method for Point and Interval Estimation of Coefficient Alpha. (February 2015) - Raykov, Tenko; Marcoulides, George A.
A direct approach to point and interval estimation of Cronbach's coefficient alpha for multiple component measuring instruments is outlined. The procedure is based on a latent variable modeling application with widely circulated software. As a by-product, using sample data the method permits ascertaining whether the population discrepancy between alpha and the composite reliability coefficient may be practically negligible for a given empirical setting. The outlined approach is illustrated with numerical data.